Benefits and Risks Associated With Aspirin Use in Patients With Diabetes for the Primary Prevention of Cardiovascular Events and Mortality: A Meta-Analysis - Ma, Hua; Gu, Qing; Niu, Huining; Li, Xiaohua; Wang, Rong (Frontiers in Endocrinology, 2021)
Objectives: A meta-analysis was conducted to assess the benefits and risks of aspirin for the primary prevention of cardiovascular disease and all-cause mortality events in adults with diabetes. Methods: An extensive and systematic search was conducted in MEDLINE (via PubMed), Cinahl (via Ebsco), Scopus, and Web of Sciences from 1988 to December 2020. A detailed literature search was conducted using aspirin, cardiovascular disease (CVD), diabetes, and efficacy to identify trials of patients with diabetes who received aspirin for primary prevention of CVD. Demographic details with the primary outcome of events and bleeding outcomes were analyzed. The Cochrane Collaboration's risk of bias tool was used to assess the methodological quality of the included studies. Random-effects meta-analysis was used to calculate the pooled odds ratio for outcomes of cardiovascular events, death, and adverse events. Results: A total of 8 studies were included with 32,024 diabetic patients; 16,001 allocated to aspirin, and 16,023 allocated to the -control group. In patients with diabetes, there was no difference between aspirin and control groups with respect to all-cause mortality, cardiovascular mortality, or bleeding events. However, MACE was significantly lower in the aspirin group compared to the control. Conclusion: Aspirin has no significant risk on primary endpoints of cardiovascular events and the bleeding outcomes in diabetic patients compared to control. However major adverse cardiovascular events are significantly lower in the aspirin group as compared to the control. Further research on the use of aspirin alone or in combination with other antiplatelet drugs is required in patients with diabetes to supplement currently available research.